2012
DOI: 10.1016/j.resinv.2012.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical preparedness for severe pneumonia with highly pathogenic avian influenza A (H5N1): Experiences with cases in Vietnam

Abstract: Understanding local H5N1 poultry outbreaks and chest radiography assist early diagnosis and initiation of antiviral treatment. Developing a network among local and tertiary care hospitals can reduce the time to initiation of treatment. CHDF and PMX hemoperfusion are possible candidates for effective treatment of ARDS with H5N1 if applied earlier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…All subtypes of FluA comprise various combinations of the H and N glycoproteins. Sixteen H subtypes (H1-H16) and nine N subtypes (N1-N9) have been characterized in avian species, while the H17N10 subtype is found in bats [3,4]. Most subtypes of FluA virus such as H5 and H7 subtypes are not pathogenic in poultry, but outbreaks in poultry and wild birds are correlated with the highly virulent FluA virus, which can cause severe economic losses owing to massive numbers of deaths of domestic poultry [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…All subtypes of FluA comprise various combinations of the H and N glycoproteins. Sixteen H subtypes (H1-H16) and nine N subtypes (N1-N9) have been characterized in avian species, while the H17N10 subtype is found in bats [3,4]. Most subtypes of FluA virus such as H5 and H7 subtypes are not pathogenic in poultry, but outbreaks in poultry and wild birds are correlated with the highly virulent FluA virus, which can cause severe economic losses owing to massive numbers of deaths of domestic poultry [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Human infections with FluA viruses are commonly associated with the human H1, H2, and H3 subtypes that can cause outbreaks of FluA virus infection, such as the seasonal H3N2 virus and the pandemic (H1N1) 2009 virus (Cox and Subbarao 2000; Chen et al 2011; Bedford et al 2015; Davlin et al 2016; Yang et al 2015). However, sporadic cases or outbreaks of the avian FluA subtypes H5N1, H7N3, H10N8, and H9N2, and the reassortant avian H7N9 virus have resulted in the direct transmission from avians to humans and have caused many deaths in humans (Kudo et al 2012; Kim et al 2012; Koopmans et al 2004; Chen et al 2013, 2014; Cheng et al 2011; Ostrowsky et al 2012; Gao et al 2013). Most patients infected with these subtypes have mild symptoms during the early stages of the disease, such as acute respiratory infections associated with fever and/or sore throat, with or without fatigue symptoms; however, the patients with H5N1 virus and reassortant avian H7N9 virus have a high mortality rate (Cheng et al 2011, 2013, 2014; Ostrowsky et al 2012; Gao et al 2013; Chong et al 2016; Kang et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, pandemic (H1N1) 2009 emerged worldwide in 2009, and the human H3N2 outbreak in 2015 resulted in substantial human infections and deaths (Bedford et al 2015; Wu et al 2014; Davlin et al 2016; Yang et al 2015). Moreover, sporadic cases or outbreaks of the avian Flu A subtype, such as H5N1, H7N7, H10N8, and H9N2, have displayed direct transmission from domestic poultry and/or wild birds to humans, especially the reassortant avian H7N9 virus from live poultry or avian outbreaks in China in 2013 (Wu et al 2014; Kudo et al 2012; Kim et al 2012; Koopmans et al 2004; Chen et al 2013, 2014; Cheng et al 2011; Ostrowsky et al 2012; Gao et al 2013). Most patients infected with these subtypes present similar symptoms with influenza-like illness (ILIs) in the early stages of disease, such as fever, fatigue and/or sore throat, severe acquired pneumonia, and even death.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study demonstrates that early initiation of antiviral treatment has a strong influence on the survival of patients with A (H5N1) infection. Kudo et al [6] have most recently reported that renal replacement therapy using Polymyxin B-immobilized polystyrene fibers (PMX) and Continuous Hemodiafiltration (CHDF) could provide a practical tool to effectively treat H5N1-infected patients with acute respiratory distress syndrome (ARDS). PMX (Toray industries Inc, Tokyo, Japan) binds endotoxin and inflammatory cytokines in both in vitro and in vivo studies [7].…”
Section: Editorialmentioning
confidence: 99%
“…Accordingly, the PaO 2 /FiO 2 ratio increased to 128 at 24 h and to 203 at 3 days after initiation of PMX hemoperfusion. Thus, renal replacement therapy using PMX and Continuous Hemodiafiltration (CHDF) provided a practical tool to effectively treat H5N1-infected patients with Acute Respiratory Distress Syndrome (ARDS) [6].…”
Section: Editorialmentioning
confidence: 99%